2011
DOI: 10.5539/ijef.v3n2p200
|View full text |Cite
|
Sign up to set email alerts
|

Profits: Mean Diverting with High Volatility

Abstract: Even though the behavior of the U.S. profit growth varies over the economic cycle that variation itself drives investor behavior and asset prices. We raise three fundamental questions which are; first, does profit growth over time exhibit a mean-reverting behavior? Second, how volatile are profits and does this volatility obscure the message of profit growth? Finally, do profit growth rates vary between decades/ sub-samples? Our efforts suggest that since 1970 the mean and standard deviation of profit growth h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…They found that companies exhibited different and significant performance trends, suggesting a variety of evolutionary structures extending well beyond the standard mean-reverting process in autoregressive models. Silvia and Iqbal (2011) also found evidence of a growth trend and structural breaks in the aggregate profit series of US companies. They argued that in a Schumpeterian world, deviations from equilibrium create rents that, once dissipated, do not bring the market back to the previous equilibrium but rather to a new one.…”
Section: The Emergence Of New Rents and The Interpretation Of Profit Dynamicsmentioning
confidence: 83%
See 1 more Smart Citation
“…They found that companies exhibited different and significant performance trends, suggesting a variety of evolutionary structures extending well beyond the standard mean-reverting process in autoregressive models. Silvia and Iqbal (2011) also found evidence of a growth trend and structural breaks in the aggregate profit series of US companies. They argued that in a Schumpeterian world, deviations from equilibrium create rents that, once dissipated, do not bring the market back to the previous equilibrium but rather to a new one.…”
Section: The Emergence Of New Rents and The Interpretation Of Profit Dynamicsmentioning
confidence: 83%
“…Companies permanently engage in processes, actions, and decisions that may influence their competitive position and that consequently may have an effect on the company’s expected profitability that goes beyond the idea of unsystematic shocks. Such an effect may be captured in a trend-based model (Cable and Jackson, 2008; Silvia and Iqbal, 2011)…”
Section: The Model: a Linear Latent Growth Curvementioning
confidence: 99%
“…Estadísticamente, la prueba ZA ha sido criticada porque suele indicar la presencia de quiebres inexistentes, i.e. -quiebres espurios‖ (Silvia e Iqbal, 2011). Por esta razón, el análisis de cambio estructural se complementa con estimaciones de la prueba de raíz unitaria Kim-Perron (KP).…”
Section: Metodología De Investigaciónunclassified